The relationship between Th1/Th2 balance and 1?,25-dihydroxyvitamin D3 in patients with nasal polyposis - Ozkara, Sule; Keles, Erol; Ilhan, Nevin; Gungor, Hilal; Kaygusuz, Irfan; Alpay, Hayrettin Cengiz (Springer, 2012)
We aimed to study Th1/Th2 cell balance by measuring the levels of cytokines IL-4, IL-10, and IFN-gamma, which play an important role in the immune response of patients with allergic rhinitis and/or nasal polyps, and determine the correlation between Th1/Th2 cell balance and 1 alpha,25-dihydroxyvitamin D-3, an active metabolite of vitamin D. The study subjects were 60 adult patients and 40 healthy volunteers. Subjects were separated into three groups: 30 patients diagnosed with nasal polyposis together with allergic rhinitis formed Group I, 30 patients with nasal polyposis but without allergic rhinitis constituted Group II, and 40 healthy volunteers without nasal polyp and/or allergic rhinitis were the control group, or Group III. IFN-gamma, IL-4, IL-10, and total IgE levels were determined in the serum samples of all patients and vitamin D-3 in their plasma. A statistically significant difference was found between the Group I and the control group in their IgE, IL-4, IL-10, IFN-gamma, and vitamin D levels (p < 0.05), while there were no such significant differences between Group II and the control group in these measurements (p > 0.05). Within Group I, vitamin D levels showed a negative correlation with IgE and IL-4 levels, and a positive correlation with IFN-gamma (p < 0.05). Within Group II, IgE levels showed a positive correlation with IL-4 and IL-10 levels (p < 0.05) and a negative correlation with IFN-gamma levels (p < 0.05). In this study, no significant relation was detected between vitamin D deficiency and nasal polyposis in the absence of allergic rhinitis. The study demonstrates that vitamin D is effective on Th1/Th2 balance in patients with allergic rhinitis and that there is a significant relation between vitamin D deficiency and allergy. These results are compatible with the possibility of an important role of vitamin D in the pathogenesis and degree of severity of allergic disease, and its capacity to control allergic disease.
Keywords: Nasal polyposis; Allergic rhinitis; Vitamin D; Th1; Th2